SEJARAH PERKEBUNAN CASSIAVERA DI PULAU SANGKAR KABUPATEN KERINCI 1970-2002 - Tetti Yeni (Universitas Batanghari Jambi, 2019)
AbstractCassiavera is an export commodity that is used to improve the taste of food, cosmetics and as a healing spice. Cassiavera planted by farmers in Pulau Sangkar, Kerinci Regency, Jambi Province, has been enjoyed internationally and is Indonesia's largest export of this crop and Kerinci itself is one of the cassiavera bases in Indonesia. However, changes in the world economy have an impact on falling cassiavera prices causing reduced income for farmers, so it is necessary to find alternative crops so that people continue to get income in the plantation sector. In 1999 the Kerinci Regency Agriculture and Plantation Service held an agricultural extension program to farmers by forming farmer groups. The Agriculture Service introduces short-term civilization to farmers namely horticultural crops. In the early stages of this transition is not easy for farmers because besides lacking skills in this case also due to the fact that so for the Sangkar Island farmers focus more attention on cassiavera which is considered very easy in its processing.Keywords: Plantation, Cassiavera, AbstrakCassiavera merupakan salah satu komoditi ekspor yang dimanfaatkan untuk meningkatkan cita rasa makan, kosmetik dan sebagai rempah penyembuh. Cassiavera yang ditanam oleh petani Pulau Sangkar Kabupaten Kerinci Provinsi Jambi ternyata telah dinikmati oleh dunia internasional dan merupakan ekspor Indonesia yang terbesar dari tanaman ini dan Kerinci sendiri merupakan salah satu basis cassiavera di Indonesia. Namun perubahan perekonomian dunia berdampak pada penurunan harga cassiavera menyebabkan pendapatan semakin berkurang bagi para petani, sehingga perlu dicari tanaman alternatif agar masyarakat tetap mendapatkan penghasilan yang di sektor perkebunan. Pada tahun 1999 Dinas Pertanian dan Perkebunan Kabupaten Kerinci mengadakan penyuluhan pertanian kepada petani dengan membentuk kelompok tani. Dinas Pertanian ini memperkenalkan pembudayaan jangka pendek kepada petani yakni tanaman holtikultura. Pada tahap awal peralihan ini bukanlah hal yang mudah bagi petani sebab disamping kurang mempunyai skil dalam hal ini juga disebabkan selama ini petani Pulau Sangkar lebih banyak memfokuskan perhatian pada cassiavera yang dianggap sangat mudah dalam pengolahanya.Kata Kunci: Perkebunan, Cassiavera,